Biopolymer-enriched B. subtilis NCIB 3610 biofilms exhibit increased erosion resistance. (2nd September 2019) - Hayta, Elif N.; Lieleg, Oliver
Abstract : By incorporating the macromolecule PGA into the matrix of B. subtilis biofilms, the superhydrophobobic properties of the material are enhanced. Abstract : The erosion resistance of bacterial biofilms can be a double-edged sword: it hampers the removal of undesired biofilms in biomedical settings, but it is necessary for beneficial biofilms to be used in aqueous environments for biotechnological applications. Whether or not a bacterial biofilm exhibits this material property depends on the bacterial species and the detailed composition of the biofilm matrix. Here, we demonstrate how the erosion resistance of B. subtilis NCIB 3610 biofilms can be enhanced by integrating foreign (bio)polymers into the matrix during biofilm growth. As a result of this artificial macromolecule addition, the engineered biofilm colonies show changes in their surface topography which, in turn, cause an alteration in the mode of surface superhydrophobicity. Surprisingly, the viscoelastic properties and permeability of the biofilms towards antibiotics remain unaffected. The method introduced here may present a promising strategy for engineering beneficial biofilms such, that they become more stable towards shear forces caused by flowing water but, at the same time, remain permeable to nutrients or other molecules.